2022
DOI: 10.1177/03000605221119376
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis reveals differentially expressed inflammatory chemokines in a rat retinal degeneration model induced by sodium iodate

Abstract: Objective Retinal degeneration (RD) is a group of serious blinding eye diseases characterized by photoreceptor cell apoptosis and progressive degeneration of retinal neurons. However, the underlying mechanism of its pathogenesis remains unclear. Methods In this study, retinal tissues from sodium iodate (NaIO3)-induced RD and control rats were collected for transcriptome analysis using RNA-sequencing (RNA-seq). Analysis of white blood cell-related parameters was conducted in patients with retinitis pigmentosa (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A number of preclinical investigations have shown that oxidative stress stimulates the initiation and amplification of inflammatory pathways in a wide range of cell types in the retina and choroid [47][48][49]. Recent research has also shown that the NaIO 3 model modulates soluble immune proteins, complement proteins, and cytokines/chemokines in a time-dependent manner, supporting the idea that this model could be used to mimic retinal inflammatory sequences [41,50]. Ldlr −/− mice fed with high-fat diet for 12 weeks had increased oxidized lipids and inflammatory markers and caused pulmonary hypertension [51], suggesting a role for LDLR and oxidized lipids in the initiation of diseases.…”
Section: Discussionmentioning
confidence: 91%
“…A number of preclinical investigations have shown that oxidative stress stimulates the initiation and amplification of inflammatory pathways in a wide range of cell types in the retina and choroid [47][48][49]. Recent research has also shown that the NaIO 3 model modulates soluble immune proteins, complement proteins, and cytokines/chemokines in a time-dependent manner, supporting the idea that this model could be used to mimic retinal inflammatory sequences [41,50]. Ldlr −/− mice fed with high-fat diet for 12 weeks had increased oxidized lipids and inflammatory markers and caused pulmonary hypertension [51], suggesting a role for LDLR and oxidized lipids in the initiation of diseases.…”
Section: Discussionmentioning
confidence: 91%